Life and death of β cells in Type 1 diabetes: A comprehensive review. (July 2016) - Wilcox, Nicholas S.; Rui, Jinxiu; Hebrok, Matthias; Herold, Kevan C.
Abstract: Type 1 diabetes (T1D) is an autoimmune disorder characterized by the destruction of insulin-producing pancreatic β cells. Immune modulators have achieved some success in modifying the course of disease progression in T1D. However, there are parallel declines in C-peptide levels in treated and control groups after initial responses. In this review, we discuss mechanisms of β cell death in T1D that involve necrosis and apoptosis. New technologies are being developed to enable visualization of insulitis and β cell mass involving positron emission transmission that identifies β cell ligands and magnetic resonance imaging that can identify vascular leakage. Molecular signatures that identify β cell derived insulin DNA that is released from dying cells have been described and applied to clinical settings. We also consider changes in β cells that occur during disease progression including the induction of DNA methyltransferases that may affect the function and differentiation of β cells. Our findings from newer data suggest that the model of chronic long standing β cell killing should be reconsidered. These studies indicate that the pathophysiology is accelerated in the peridiagnosis period and manifest by increased rates of β cell killing and insulin secretory impairments over a shorter period than previously thought. Finally, we consider cellular explanations to account for the ongoing loss of insulin production despite continued immune therapy that may identify potential targets for treatment. The progressive decline in β cell function raises the question as to whether β cell failure that is independent of immune attack may be involved. Highlights: During progression of Type 1 diabetes beta cells most likely die from a combination of necrosis and apoptosis. Methods to visualize beta cell inflammation and beta cell mass are being developed. Molecular techniques have been applied to identify beta cell killing in vivo . Studies with these methods suggests revision of previous models of the pathogenesis of the disease. The cause of long term beta cell loss remains unclear. It is possible that ongoing beta cell destruction is intrinsic. The basis for the long term loss of beta cell remains unclear. It is possible that ongoing beta cell destruction is intrinsic.